Increased PD-1+Foxp3+ γδ T cells associate with poor overall survival for patients with acute myeloid leukemia - Zheng, Jiamian; Qiu, Dan; Jiang, Xuan; Zhao, Yun; Zhao, Haotian; Wu, Xiaofang; Chen, Jie; Lai, Jing; Zhang, Wenbin; Li, Xutong; Li, Yangqiu; Wu, Xiuli; et al. (Frontiers in Oncology, 2022)
γδ T cells are essential for anti-leukemia function in immunotherapy, however, γδ T cells have different functional subsets, including regulatory cell subsets expressing the Foxp3. Whether they are correlated with immune-checkpoint mediated T cell immune dysfunction remains unknown in patients with acute myeloid leukemia (AML). In this study, we found that PD-1 gene was positively correlated with FOXP3 gene and highly co-expressed PD-1 and FOXP3 genes were associated with poor overall survival (OS) from TCGA database. Then, we detected a skewed distribution of γδ T cells with increased Vδ1 and decreased Vδ2 T cell subsets in AML. Moreover, significantly higher percentages of PD-1+ γδ, Foxp3+ γδ, and PD-1+Foxp3+ γδ T cells were detected in de novo AML patients compared with healthy individuals. More importantly, AML patients containing higher PD-1+Foxp3+ γδ T cells had lower OS, which might be a potential therapeutic target for leukemia immunotherapy.